Cross-border or Online - Tax Competition with Mobile Consumers under Destination and Origin Principle - Laura Birg (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper studies the effect of an online retailer on spatial tax competition with mobile consumers. If taxation for online purchases follows the destination principle, in many cases, the entry of the online retailer mitigates tax competition. If taxation for online purchases follows the origin principle, the entry of the online retailer typically enhances tax competition. Cooperation between government reverses this effect. For sufficiently low (high) online shopping costs, welfare in the online retailer's home country is higher under the origin (destination) principle, while welfare in the other country is higher under the destination (origin) principle. Global welfare is higher under the destination principle.
Keywords: F12; H20; L13; 330; tax competition; cross-border shopping; online retailer; destination principle; origin principle